Analyzing the Threat of Foreign Refugees Existence in Indonesia through the Intelligence Perspective - Purwoko, Bayu; Hanita, Margaretha; Riyanta, Stanislaus (Indonesian Journal of Multidisciplinary Science, 2023)
Conflicts that occur in various countries indirectly affect Indonesia, namely with population migration for security reasons or also called refugees abroad (refugee). Until now, the number of foreign refugees in Indonesia as of May 2023 has reached 12,704 people. This study aims to analyze the threat of refugee existence in Indonesia by collecting data related to the prominence of Afghan and Rohingya refugees in Indonesia with descriptive qualitative methods referring to threat analysis. The research used a descriptive approach with qualitative data from relevant literatures. The results showed that the existence of refugees has the potential to become a threat as a result of prominent factors such as intention, circumstance, and vulnerability. The intention factor results from refugees who have long lived in Indonesia in shelters that have a saturation point. The situation factor by the main issue is the slow process of resstelement and voluntary repatriation into problems for which there is no definite solution and several relevant issues including Australia's interest in handling overseas refugees in Indonesia, religious and cultural similarities in hosting in Indonesia and the role of trafficking syndicates in the arrival of overseas refugees in Indonesia. Vulnerability factors include gaps in the assessment process for determining refugee status and procedures for handling migrants with final reject status as well as the role of trafficking syndicates.